Analysis of Environmental Pollution in Developing Countries - Adeuti, Dr. Bosede Remilekun (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
Environmental pollution is a major concern in developing countries of the world, especially in Nigeria. This issue of pollution is a terrible negative vibe or influence on all the living things and the environment. Pollution of the environment via air, land and water by human activities is detrimental to the existence of all living things within the society which is not an acceptable development at all. Air pollution is caused by several factors such as emission from motor vehicles, industrial activities, volcanic eruption, emitting poisonous, forest fire, deforestation, bush burning and cosmic clouds of dusts. Soil pollution is also caused by factors such as oil spillage, human erosion and contamination by hazardous substances. Water pollution is caused by oil discharge from vessels, dumping from ships and aircrafts, wastes disposal from land, oil spillage, organic sources and other means of polluting the environment. Pollution is a vital environmental disaster due to the fact that some known and unknown diseases are discovered and might be difficult to subdue. In this article, environmental pollution will be discussed under three classes of pollution that is the water, the soil, and the air and their impact on human health; also needed measures to reduce pollution in Nigeria as a case study.